Associations of daily steps and step intensity with peripheral arterial disease in Chinese community-dwelling older women - Chenfei Li; Litao Du; Xiangli Xue; Na Zhao; Qiang He; Si Chen; Xianliang Zhang (Experimental Gerontology)
Aims: This study aims to investigate the associations of objectively measured daily steps and step intensity with peripheral arterial disease (PAD) in Chinese community-dwelling older women. Methods: Cross-sectional data were derived from the baseline survey of the Physical Activity and Health in Older Women Study. Peripheral arterial disease was evaluated through ankle-brachial index (ABI), ABI ≤ 0.9 was defined as cut-off point. Daily steps and step intensity were measured via tri-axial accelerometers. Multivariate logistic regression was used to investigate associations of step variable with PAD. Receiver operating characteristic (ROC) analysis was applied to identify an optimal cut-off value for step variables to screen PAD. Results: After adjusting for confounding factors, it was found that daily steps was not independently associated with PAD, and brisk steps, peak 30 as well as peak 60, were significantly associated with PAD, with ORs of 0.68 (0.50–0.93), 0.71 (0.52–0.96) and 0.60 (0.40–0.90), respectively. The optimal cut-off values for brisk steps, peak 30 and 60 screening PAD were 952.3 steps, 76.7 steps/min and 51.8 steps/min, respectively. Conclusions: Step intensity rather than daily steps was independently associated with PAD in Chinese community-dwelling older women. Increasing the intensity during walking may be a viable strategy to reduce the risk of PAD in self-care and cardiovascular nursing.